Kritik Yuridis Atas Proses Pembentukan Uu Tindak Pidana Kekerasan Seksual : Antara Legitimasi Partisipasi Publik Dan Desakan Perlindungan Hak Asasi Manusia - Kaharuddin Kaharuddin; Kayla Mahiya Putri Wibowo; Karina Salma Nurlaila; Dinda Azka Aulia (Journal of Innovative and Creativity, 2026)
Sexual violence in Indonesia has increased significantly, prompting the government to enact Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS) to provide legal protection for victims. This study critically examines the law’s formation process with a focus on public participation legitimacy and human rights fulfillment. Using a qualitative normative juridical approach, the research analyzes legal documents, legislative records, and related literature from 2021 to 2025. The population includes all relevant legal and academic sources, with purposive sampling applied. Data were analyzed thematically through descriptive and analytical techniques. The findings reveal that while public participation involving women activists and civil organizations strengthened procedural legitimacy, inclusivity and substantive influence in legislation content remain limited due to political pressures and ideological conflicts. The study concludes that despite advancing gender-based legal protection, challenges remain in implementation and ensuring equitable representation. It recommends enhancing transparency, continuous public engagement, and capacity building among law enforcement. This research contributes to understanding legislative processes in human rights protection contexts.